The Effect Of Artificial Intelligence On Smart Customer Experience With Moderation Of Technology Readiness (Case Study On Go Food Application) - Monica Irene Putri Bagaskara; Nurvita Trianasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Artificial Intelligence in business creates great opportunities in the field of marketing because as it matures Artificial Intelligence makes it easier to identify and understand consumers. In 2015 Gojek launched an online-based food ordering application service under the name GoFood. Consumers can order food using Go Food by selecting the food or drink they want to buy. However, customer satisfaction is also influenced by the community's readiness to adapt to the fast development of technology, which is called Technology Readiness, where everyone has individual personality traits related to their use of technology. This study examines the dimensions of AI explaining the relationship between Artificial Intelligence (AI) stimuli and Smart Customer Experience. This type of research uses quantitative methods. In this research, the moderating variable is Technology Readiness, with the independent variable being AI stimuli and the dependent variable being Smart Customer Experience. There are findings in the research that the two dimensions of Artificial Intelligence (AI) (namely passion and utility) have a significant positive impact on the Smart Customer Experience; the moderating effect of the Technology Readiness dimension (ie optimism and discomfort) is significantly different, the Smart Customer Experience has a significant positive impact on consumer word-of-mouth (WOM) intentions.